Scar after caesarean section - possibilities of physiotherapy - Wawryków, Agata; Korabiusz, Katarzyna; Torbé, Dorota; Torbé, Andrzej; Lubkowska, Anna; Wawryków, Paweł (Journal of Education, Health and Sport, 2017)
Caesarean section delivery is currently the most frequent obstetrical operation. Healing of the surgical wounds constitutes the substantial medical problem. The caesarean section wound usually requires the special care because this operation is often performed in the not-planned time, in general in the great hurry. Complications of healing of caesarean scars may cause serious asymmetries of the body and even disturbances of the walk. From the aesthetic point of view, the appearance of the scar of the post-operative skin is also very important for the women. Physiotherapy offers several methods of care on the skin scar which include support of the physiological process of its creating and counteraction for adverse effects of its forming. In this article the rules of education of patients and methods of manual work with the scar, as well as other supporting methods were described.